2019
DOI: 10.1097/meg.0000000000001283
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and costs of treating hepatitis C patients with second-generation direct-acting antivirals: results from the German Hepatitis C-Registry

Abstract: Objective Chronic hepatitis C virus infection is associated with a significant health burden. Long-term consequences are the development of liver cirrhosis and hepatocellular carcinoma. The introduction of direct-acting antivirals (DAA) has led to an increase in sustained virologic response rates (SVR), but is accompanied by higher treatment costs. The aim of this study was to assess the outcomes and costs of treating hepatitis C virus infected patients with DAAs in clinical practice in Germany. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…Since the introduction of first DAAs prices have significantly decreased. We assumed average treatment costs of 34,000 EUR reflecting recent costs developments [27, 28]. An annual price reduction of 4% for the DAA was also taken into account.…”
Section: Methodsmentioning
confidence: 99%
“…Since the introduction of first DAAs prices have significantly decreased. We assumed average treatment costs of 34,000 EUR reflecting recent costs developments [27, 28]. An annual price reduction of 4% for the DAA was also taken into account.…”
Section: Methodsmentioning
confidence: 99%
“…Adverse events (AE) may occur during HCV treatment. While previous German real-world studies showed that 70-90 % of patients receiving interferon-containing regimens had at least one nonsevere AE and 4-11 % had a severe AE during treatment [29,30], recent studies in patients receiving predominantly interferon-free regimens show non-severe AE (58 %) and severe AE (3 %) less frequently, confirming better tolerability of interferon-free regimens [12]. In our sample, which received predominantly interferon-free regimens, non-severe AE occurred in half of the sample and severe AE in 4 %.…”
Section: Safety Summary and Adverse Events During Treatmentmentioning
confidence: 87%
“…The average pharmaceutical costs summed up to € 48 470, in a previous analysis (02/2014-02/2017) the costs amounted to € 67 131 [12]. The costs vary between cirrhosis-status (€ 42 530 for non-cirrhotic and € 60 802 for cirrhotic) and sub-populations (€ 49 282 for non-HIV-population and € 44 827 for HIV = infected and/or OST patients).…”
Section: Pharmaceutical Costs and Costs Per Svrmentioning
confidence: 88%
See 1 more Smart Citation
“…Stringente Qualitätssicherungsmaßnahmen inklusive zentralem und Vor-Ort-Monitoring sowie die unabhängige Leitung unter dem Dach der Deutschen Leberstiftung in Zusammenarbeit mit dem Berufsverband Niedergelassener Gastroenterologen Deutschlands e. V. (bng) begründet die Wertigkeit der Befunde. In den letzten Jahren konnten neben zahlreichen Kongressbeiträgen bereits 13 Originalarbeiten publiziert werden, die einzelne HCV-Genotypen [9 -11], bestimmte Therapieregime [12,13], besondere Patientenpopulationen wie HCV/HIV ko-infizierte [14,15], substituierte [16], zur Transplantation gelistete [17] oder ältere Patienten [18] oder andere Fragestellungen (virolo-gische Befunde [19], Gesundheitsökonomie [20], Fibrosemarker [21]) behandelt haben. Die Hauptbefunde der hier vorgestellten aktuellen Gesamtauswertung lassen sich wie folgt zusammenfassen: (i) Die Patientencharakteristika im DHC-R haben sich in den letzten vier Jahren deutlich gewandelt, (ii) der Anteil von Patienten mit Leberzirrhose, die in Deutschland antiviral behandelt werden müssen, nimmt kontinuierlich ab; (iii) Patienten mit einer gleichzeitig bestehenden Substitutionsbehandlung und/oder Patienten nach aktivem Drogenkonsum nehmen einen immer größeren Anteil am Hepatitis-C-Kollektiv in Deutschland ein; (iv) die hohe Effektivität und Sicherheit der interferonfreien Therapie der Hepatitis C konnte im DHC-R und damit auch außerhalb von klinischen Studien eindrucksvoll bestätigt werden.…”
Section: Diskussionunclassified